2019
DOI: 10.1007/s42773-019-00007-4
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-step synthesis of graphitic carbon nitride-modified biochar for the removal of reactive red 120 through adsorption and photocatalytic degradation

Abstract: Converting waste biomass into value-added biochar has been considered as a green and sustainable strategy for resource management and pollution control. In this study, graphitic carbon nitride (g-C 3 N 4 ) modified biochars (BCs) were produced through one-pot pyrolysis of urea and hickory chips in differential ratios at 520 °C. The resulting BC/g-C 3 N 4 composites were evaluated in laboratory for their physicochemical, adsorptive, and photocatalytic properties. The characterization tests showed the successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The BC/C 3 N 4 composites showed much higher adsorption capacity of reactive red 120 (RR120) than pristine biochar due to the strong electrostatic attrition between N-containing groups of C 3 N 4 and anionic RR120. The surface adsorbed RR120 was then photocatalytically degraded by the free radicals under visible light irradiation under natural conditions (Zheng et al 2019).…”
Section: Catalytic Degradation Of Organic Pollutantsmentioning
confidence: 99%
“…The BC/C 3 N 4 composites showed much higher adsorption capacity of reactive red 120 (RR120) than pristine biochar due to the strong electrostatic attrition between N-containing groups of C 3 N 4 and anionic RR120. The surface adsorbed RR120 was then photocatalytically degraded by the free radicals under visible light irradiation under natural conditions (Zheng et al 2019).…”
Section: Catalytic Degradation Of Organic Pollutantsmentioning
confidence: 99%
“…In most cases, after the combination, the S BET of the BCPs is higher than that of the original BC. However, it was found that the mesopores and micropores of BC may be clogged due to the aggregation of semiconductors, thus inducing the decrease of the S BET [62,72].…”
Section: Morphology and Surface Areamentioning
confidence: 99%
“…Due to the greater absorption of the visible spectrum, BC elevated the quantum efficiency, charge separation, and generation of free radicals. Zheng et al [72] synthesized BC-based g-C 3 N 4 via one-pot pyrolysis with different mass ratio. g-C 3 N 4 modification can expand biochar's capacity.…”
Section: G-c 3 N 4 -Bcpsmentioning
confidence: 99%
“…Preparation of biochar-based graphitic carbon nitride was carried out according to the previously reported procedure with some modification [ 75 , 76 ]. In this work, Zinnia grandiflora petals, collected from the north of Iran, were utilized for the first time as biosources.…”
Section: Methodsmentioning
confidence: 99%